2021
DOI: 10.1038/s41598-021-89034-5
|View full text |Cite
|
Sign up to set email alerts
|

First comprehensive quantification of annual land use/cover from 1990 to 2020 across mainland Vietnam

Abstract: Extensive studies have highlighted a need for frequently consistent land cover information for interdisciplinary studies. This paper proposes a comprehensive framework for the automatic production of the first Vietnam-wide annual land use/land cover (LULC) data sets (VLUCDs) from 1990 to 2020, using available remotely sensed and inventory data. Classification accuracies ranged from 85.7 ± 1.3 to 92.0 ± 1.2% with the primary dominant LULC and 77.6 ± 1.2% to 84.7 ± 1.1% with the secondary dominant LULC. This con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 91 publications
1
40
2
Order By: Relevance
“…Next, Random Forest Classifiers were used for aquaculture area mapping in the Pearl River Basin, with an overall accuracy of 89.5%. Phan et al [26] developed a framework to monitor the yearly LULC of Vietnam over the past 3 decades. Landsat and Sentinel SAR images were obtained and pre-processed on GEE and used the Random Forest classifier to obtain the area of LULC classes, one of which is the aquaculture area.…”
Section: Combination Of Optical and Microwave Datamentioning
confidence: 99%
“…Next, Random Forest Classifiers were used for aquaculture area mapping in the Pearl River Basin, with an overall accuracy of 89.5%. Phan et al [26] developed a framework to monitor the yearly LULC of Vietnam over the past 3 decades. Landsat and Sentinel SAR images were obtained and pre-processed on GEE and used the Random Forest classifier to obtain the area of LULC classes, one of which is the aquaculture area.…”
Section: Combination Of Optical and Microwave Datamentioning
confidence: 99%
“…Different land use types will directly affect land use volatility [37]. Considering there is a large number of shifting cultivation behaviors in the study area, in order to veal the relationship between land use volatility and current land use/cover types (tha land use types in 2018), dividing land use types into land cover types closely relate shifting cultivation could be more feasible, considering the local land use characteris The land classification results were derived from our previous research [36].…”
Section: Land Use/cover Mapsmentioning
confidence: 99%
“…Considering the agglomeration effect of land use [36], in order to analyze the impact of large land use volatility on the surrounding land, we measured the distance from small land use volatility (NBR < 500, that is, the change values of NBR were less than 500, the same below) to large land use volatility (NBR > 500), and finally completed the cluster/outlier analysis of land use volatility. Land use/cover types also have a significant impact on land use volatility [37], both in terms of change cycle and change time. Therefore, we further coupled the spatial relationship between the latest land use types and different land use volatility to reveal how land use affected the land use volatility (Figure 4).…”
Section: Research Frameworkmentioning
confidence: 99%
“…LULC studies are effective in providing valuable data needed for the assessment of qualitative and quantitative changes brought by human activities that have an adverse bearing on the forest ecosystems and biodiversity (Cheng, Chen et al, 2019;Kumne and Samanta, 2019;Sharma, Chaudhry et al, 2017;Srivastava, Singh et al, 2020). Hadagha, Farhi et al (2021) investigated the impact of urbanization on palm groves and desert oasis ecosystems while Phan, Trung et al (2021) reported a tenfold increase in urban areas across Vietnam which came at the expanse of the productive agricultural ecosystem. Some researchers have also used GIS as a tool to quantify the negative impact of urbanization on ecosystem services such as carbon sequestration (Han, Y., Kang et al, 2018), impact on land surface temperature (Hussain and Karuppannan, 2021) and habitat quality (He, Huang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%